2014
DOI: 10.1016/j.corsci.2014.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Low apparent valence of Mg during corrosion

Abstract: Our recent data on Mg corrosion has been reanalysed because of the recent criticism that our previous data analysis was inadequate. Re-analysis leads to similar conclusions as previously. The apparent valence of Mg during corrosion was in each case less than 2.0, and in many cases less than 1.0. Moreover, these values were probably over-estimates. The low values were consistent with the evolving hydrogen gas acting as an insulator, so that the corrosion of parts of the specimen could occur isolated from the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 18 publications
(70 reference statements)
2
57
0
Order By: Relevance
“…SANS could also potentially provide new insight into anodic film formation relative to the current debate regarding the mechanism of the negative difference effect for Mg, whereby H 2 evolution is observed to increase with increasing anodic potential. Knowledge gained by ex-situ or in-situ SANS study of the evolution of surface area/roughness vs. potential and/or time may help clarify the proposed mechanisms, for which filamentous/dendritic corrosion products have been reported 20,35,[61][62][63][64][65][66] …”
Section: Discussionmentioning
confidence: 99%
“…SANS could also potentially provide new insight into anodic film formation relative to the current debate regarding the mechanism of the negative difference effect for Mg, whereby H 2 evolution is observed to increase with increasing anodic potential. Knowledge gained by ex-situ or in-situ SANS study of the evolution of surface area/roughness vs. potential and/or time may help clarify the proposed mechanisms, for which filamentous/dendritic corrosion products have been reported 20,35,[61][62][63][64][65][66] …”
Section: Discussionmentioning
confidence: 99%
“…6 This phenomenon confounds the understanding of Mg dissolution mechanisms, establishment of a Tafel law and other reaction kinetic parameters, as well as other issues including accurate analysis of corrosion rates from electrochemical impedance spectroscopy (EIS). [7][8][9] There are several theories purporting to explain the origins of the NDE among which include noble impurity element enrichment, 10,11 non-faradaic mass loss via metal spalling, 12,13 formation and dissolution of hydrides and partially protective films, [14][15][16][17] and univalent Mg based dissolution followed by further oxidation of Mg + →Mg 2+ in solution (leading to hydrogen evolution from the reduction of water away from the electrode in the electrolyte); 18 however, no consensus has been reached on the physical origins of the NDE.…”
mentioning
confidence: 99%
“…Atrens et al [4,6] and Shi and Atrens [7,8] reviewed the available experimental evidence and concluded that this uni-positive Mg + reaction sequence was consistent with the available evidence regarding the details of Mg corrosion, in particular (i) that Mg corrodes with an apparent valence of less than 2.0 [9,10], and (ii) that the amount of evolved hydrogen increases with increasing anodic polarisation [4,7,8]. The fact that Mg corrodes with an apparent valence of less than 2.0 is explained by the fact that the corrosion is only partly electrochemical and that there is the dissolution reaction given by Eq.…”
Section: Issues To Be Addressedmentioning
confidence: 72%
“…A direct consequence of these assumptions is that the increased exchange current density reaction sequence predicts that the apparent valence of Mg during corrosion is always equal to 2.0. However, there is compelling evidence that the apparent valence of Mg is less than 2.0 [9,10,[31][32][33].…”
Section: Issues To Be Addressedmentioning
confidence: 99%
See 1 more Smart Citation